IMPLEMENTASI KEPEMIMPINAN SITUASIONAL DALAM MENGELOLA ANAK BERKEBUTUHAN KHUSUS DI SD KRISTEN 01 SALATIGA - Prajna Angger Kusuma; Yari Dwikurnaningsih; Herry Sanoto (STKIP Subang, 2026)
This study aims to analyze the implementation of the principal’s situational leadership in enhancing teachers’ readiness to manage students with special needs at SD Kristen 01 Salatiga. The research employed a qualitative approach using a case study design. The participants consisted of the principal and six classroom teachers with varying levels of teaching experience. Data were collected through semi-structured interviews, academic supervision observations, and document analysis of the Special Assistance Program and students’ academic progress reports.Data analysis was conducted using the interactive model of Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña, which includes data reduction, data display, and conclusion drawing and verification. The findings indicate that the principal applied four situational leadership styles directing, coaching, supporting, and delegating adaptively according to teachers’ developmental levels (D1–D4). The implementation of these leadership practices contributed to the improvement of inclusive pedagogical competence, differentiated instruction skills, equity based flexible assessment, and the strengthening of a collaborative culture within a professional learning community. Despite challenges such as time constraints and variations in teachers’ psychological readiness, situational leadership proved to be an effective strategy in fostering a sustainable inclusive school culture. This study affirms that context-based adaptive leadership is a key factor in strengthening inclusive education practices at the elementary school level.